ASSESSING SUSCEPTIBILITY TO CHROMIUM CARBIDE PRECIPITATION IN Cr-Mn AUSTENITIC STAINLESS STEEL WELDS - M. O. H. Amuda; Enumah, K.S Osoba, L.O.; M. A. Onitiri (UNILAG Journal of Medicine, Science and Technology, 2019)
Chromium-manganese austenitic stainless steel is a low cost grade with metallurgical and mechanical properties approximating a standard nickel-chromium austenitic stainless steel.  It serves as a good substitute to the standard nickel-chromium grade owing to the high cost of nickel. But, there is little information on its weldability particularly the influence of welding parameters on chromium carbide precipitation in the heat affected zone. This limits its structural application through fusion welding. Therefore, in this paper, carbide precipitation in chromium-manganese austenitic stainless steel welds was investigated in the heat input range 180 - 300 J/mm under different combinations of arc current and welding speeds. Microstructural analysis after 10% oxalic acid electrolytic etch revealed that increasing heat input produced significant changes in microstructure of the welds with wider sensitized structure at heat input greater than 206 J/mm. Microstructure of welds produced at heat input lower than 206 J/mm was free of chromium carbide precipitation. This level of heat input which corresponds to arc current of 110 -125A and welding speeds in the range 319- 395 mm/min show that sensitized region associated with chromium carbide precipitation can be safely avoided during fusion welding of this grade of austenitic stainless steel through carefully selected welding parameters